Hypolimnetic oxygenation of water supply reservoirs using bubble plume diffusers. (3rd July 2019) - Mobley, Mark; Gantzer, Paul; Benskin, Pam; Hannoun, Imad; McMahon, Susan; Austin, David; Scharf, Roger
Abstract: Mobley M, Gantzer P, Benskin P, Hannoun I, McMahon S, Austin D, Scharf R. 2019. Hypolimnetic oxygenation of water supply reservoirs using bubble plume diffusers. Lake Reserv Manage. 35:247–265. Hypolimnetic oxygenation of water supply reservoirs improves water quality by preventing anoxia. This article summarizes the operational results using linear bubble plume diffuser hypolimnetic oxygenation systems installed in water supply reservoirs. The results obtained for 8 sites demonstrate that diffuser technology was effective at increasing hypolimnetic dissolved oxygen (DO) and spreading it to blanket sediments. The diffuser systems maintained increased DO in the hypolimnion during successive years of operation at every site. Improved oxygen levels reduced anoxic products and nutrients to mitigate the causes of taste and odor in the water supplied to water treatment facilities. This yielded additional treatment capacity, reduced treatment costs, and provided alternatives to water treatment plant modifications. The diffuser systems provide a simple and effective hypolimnetic oxygenation system, with 19 in operation. The hypolimnetic oxygenation systems (HOS) functions without a water pump and can obtain favorable oxygen transfer efficiencies. The diffusers are installed and maintained from the surface without divers. Diffusers provide an economical means to distribute oxygen input over large areas of the reservoir hypolimnion. Diffuser system installation costs run between $0.5M and $2.5M ($40 to $800 per hectare meter), with annual operating costs between $30K and $140K ($5 to $36 per hectare meter). Capital and operational costs vary depending on site specific conditions. With diffuser oxygenation, customer complaints were reduced and, in some cases, substantial monetary savings were realized by reduced treatment costs. Our results demonstrate that diffusers are a cost-effective treatment option for water supply reservoirs in which anoxia induces water quality problems.